Preschool children's social skills, problem behaviors, academic self-esteem and teacher-child relationship: a serial mediation model - Tutkun, Cansu; Eskidemir Meral, Seda (Frontiers in Psychology, 2025)
IntroductionResearch has shown that children's social skills have effects on their problem behaviors. However, the mechanisms through which social skills contribute to reducing problem behaviors need further clarification.MethodsThis study examined the relationship between preschool children's social skills and problem behaviors, as well as the independent and serial mediating roles of academic self-esteem and teacher-child relationship in this relationship. The study included 382 children aged 3–5 years, randomly selected in Türkiye.Results and discussionAs a result of the study: (1) there was a significant and negative relationship between problem behaviors and social skills, academic self-esteem and teacher-child relationship; (2) the mediating role of academic self-esteem and teacher-child relationship in the relationship between social skills and problem behaviors was supported; and (3) the serial mediating role of academic self-esteem and teacher-child relationship in the effect of social skills on problem behaviors, respectively, was found. These findings indicated that children's social skills may help to increase their academic self-esteem, improve the teacher-child relationship, and thus reduce their problem behaviors. Therefore, these results have important implications for designing interventions to increase preschool children's social skills, academic self-esteem, and teacher-child relationship, as well as to prevent the early development of problem behaviors.